2018
DOI: 10.2172/1471714
|View full text |Cite
|
Sign up to set email alerts
|

Licensing Modernization Project for Advanced Reactor Technologies: FY 2018 Project Status Report

Abstract: The promise of new nuclear technology and the future of commercial power in the United States (U.S.) are linked to the existence of an efficient and safetyfocused regulatory review and licensing process. With an appropriate regulatory framework, reactor suppliers and regulators can design, license, and build advanced reactor units more efficiently and thereby help meet the growing need for clean and reliable energy.To help address the challenge of maintaining compatibility between the regulatory environment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…To determine the toxicity of manufactured nanomaterials, we chose 14 types of manufactured nanomaterials among those proposed by OECD, although the sizes of these materials were not prescribed. The nanomaterials were chosen for this experiment due to their frequency of use in the industry and research [3,[11][12][13][14][15][16][17][18]. The 14 types are Al 2 O 3 (99%), CeO 2 (>99.9%), gold (>99.9%), iron (>99%) silver (>99.9%), SiO 2 (>99.5%), and ZnO (99%), all purchased from KoreaNano (Gwangmyeong, Korea), as well as MWCNTs (>98% carbon basis), dendrimers (G4-PAMAM dendrimer, 10wt.% in methanol), nanoclays (bentonite), and TiO2 (P25, >99.5%) purchased from Sigma-Aldrich (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the toxicity of manufactured nanomaterials, we chose 14 types of manufactured nanomaterials among those proposed by OECD, although the sizes of these materials were not prescribed. The nanomaterials were chosen for this experiment due to their frequency of use in the industry and research [3,[11][12][13][14][15][16][17][18]. The 14 types are Al 2 O 3 (99%), CeO 2 (>99.9%), gold (>99.9%), iron (>99%) silver (>99.9%), SiO 2 (>99.5%), and ZnO (99%), all purchased from KoreaNano (Gwangmyeong, Korea), as well as MWCNTs (>98% carbon basis), dendrimers (G4-PAMAM dendrimer, 10wt.% in methanol), nanoclays (bentonite), and TiO2 (P25, >99.5%) purchased from Sigma-Aldrich (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, carbon black (>99%) was purchased from Uninanotech (Yongin, Korea), SWCNTs (>95%) from Carbon Nanotech (Pohang, Korea), and fullerene (C60, 99%) from Alfa Aesar (Haverhill, MA, USA). Additionally, physical and chemical properties of manufactured nanomaterials used in this study are shown in Table 1 [3,[11][12][13][14][15][16][17][18].…”
Section: Methodsmentioning
confidence: 99%
“…However, as the mongoose population declined, annual trap catch fell from 946 animals in 2008 to a single animal in 2018. During the same period, 102 mongooses were tracked by dog-handler teams to their dens, where they were captured by the dog handlers (Abe 2013;Glen and Hoshino 2020;MoE 2021).…”
Section: Case Study 2: Mongoose Eradication On Japanese Islandsmentioning
confidence: 99%
“…The NRC describes a "functional containment" approach as the full set of barriers designed to prevent any release of radioactive material into the environment. Hence, the functional containment approach can shift the nuclear plant design from satisfying rigid LWR-style prescriptive requirements toward considering multiple possible solutions in a TI-RIPB manner (Moe 2018).…”
Section: Functional Containmentmentioning
confidence: 99%